Beyond the Limitation Period: Legal Protection of Freehold Land Titles and the Tug-of-War Between Certainty and Substantive Justice in Indonesia - Restu Adi Putra; Irham Rahman; Divi Kusumaningrum (Faculty of Law, University of Dr. Soetomo, 2026)
A Freehold Title (Sertifikat Hak Milik) serves as the primary instrument in the land registration system, designed to provide legal certainty and protection for land rights holders. Nevertheless, the legal protection afforded to certificate holders following the expiration of the limitation period—as stipulated in Article 32, paragraph (2) of Government Regulation Number 24 of 1997—remains a subject of debate. This issue becomes particularly contentious when the legal certainty inherent in the certificate clashes with demands for substantive justice, often arising from alleged legal defects in its issuance. This study aims to analyze the legal protection of Freehold Title holders after the limitation period expires, viewed through the lens of balancing legal certainty and substantive justice within Indonesian agrarian law. Employing a normative legal research methodology, this study utilizes both statutory and conceptual approaches. Primary, secondary, and tertiary legal materials are analyzed prescriptively using qualitative techniques. The findings indicate that legal protection for Freehold Title holders post-limitation period cannot be granted absolutely based solely on the possession of the certificate and the passage of the five-year timeframe. Instead, protection must be administered proportionally. This requires a thorough examination of the certificate's issuance legality, the rights holder's good faith, the actual physical possession of the land, and the strict absence of fraud, abuse of authority, or fundamental legal defects. Ultimately, this research proposes a legal protection model grounded in the equilibrium between legal certainty and substantive justice, serving as a framework to protect certificate holders without compromising the imperatives of justice within Indonesian land law.